TIC for informal caregivers of elderly people with palliative care (European Journal of Health Research, 2017)
In recent years there has been an increase in palliative care at home. This has mainly due to a lack of resources in the health system. In addition, we can see that the conditions of this care is increasingly complex due to the increased length of the terminally ill, the lack of information presented by informal caregivers and difficulty of care. The objective of this project is to provide information through instruments adapted to support informal caregivers of terminally ill patients to provide them with security and knowledge also to provide their care at home.  We searched several databases on the documents and palliative care focused on informal caregivers themselves. Subsequently it became a new literature search on the most common symptoms presented by the terminally ill. After reviewing all the information obtained initially this resulted in the development of a manual for informal caregivers, which includes the basics of palliative care. Secondly, the manual was made available through ICT to which a website is created: www.cuidadospaliativosweb.com. Finally the facts gathered are discussed and new lines of research to carers that can provide quality care and appropriate to the needs of caring for the sick are proposed.
Keywords: Palliative care; terminally ill; home nursing; caregivers; dependency